(untitled) (LICERE - Revista do Programa de Pós-graduação Interdisciplinar em Estudos do Lazer, 2014)
Umberto Boccioni, Dynamism of a Soccer Player, 1913 Oil on canvas, 193.2 x 201 cm The Museum of Modern Art